The antecedents of the codification of International Civil Procedure Law in America: is America a genuine legal laboratory or the dream of the comparative scientist? (Ágora Journal, 2025)
History demonstrates that in the efforts to harmonize Private International Law (PIL) rules, the Americas, through the first processes of international codification developed between the 19th and 20th centuries, and the new American republics were protagonists of the initial challenges in this field. This article analyzes the historical background of the codification movement, particularly from the perspective of International Civil Procedural Law (ICPL), an area that evidenced complex and dynamic interactions between agreements, reservations, objections, and abstentions of the involved States. In this context, the need arises to examine and describe the historical, legal, and political factors that explain both the convergences and divergences in relations between countries, as well as how these factors conditioned the evolution and separation of Private International Law codification during this period. Following the timeline of the American congresses and the adoption of their treaties, it will be demonstrated whether the region became an "authentic legal laboratory" or the comparatist's dream. Finally, the role of Brazil will be observed, whose stance characterized by prudent and moderate participation notably influenced the regional dynamics of American legal codification.
Keywords: Americas; Codification; Private Internacional Law; internacional Civil Procedural Law; Laboratory; Treaties.